ANALISIS KECUKUPAN MODAL, RISIKO KREDIT, EFISIENSI OPERASIONAL, PENDAPATAN DARI BUNGA DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - E Janrosl, Viola Syukrina; Yuliani, Yuliani (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study aims to test and provide empirical analysis of the ratio capital adequacyas measured by capital adequacy ratio (CAR), credit risk as measured by nonperforming loan (NPL), operational efficiency as measured by BOPO, interestincome as measured by the net interest margin (NIM) and liquidity as measured byloan to deposit ratio (LDR) to profitability as measured by return on assets (ROA).The population of this research are all banking companies listed in Indonesian StockExchange (IDX) from 2010-2014. While the sample was determined by the methodof purposive sampling to obtained a sample of 26 companies. The results of thisstudy found that the variable of CAR and NPL has no significant effect on ROA.While other variables, the BOPO, NIM, LDR foundly has significant effect on ROA. Ftest results showed variable level of CAR, NPL, BOPO, NIM and LDR silmuntantly,significant effect on ROA.